Haemodynamics during liver transplantation in familial amyloidotic polyneuropathy: study of the intraoperative cardiocirculatory data of 50 patients - Viana, JS (1999)
BACKGROUND: Circulatory instability frequently complicates liver transplantation for familial amyloidotic polyneuropathy (FAP) and may be a source of surgical morbidity and mortality. OBJECTIVE: To evaluate FAP intraoperative haemodynamic data and their relation to the duration of surgery, and need for anaesthetic drugs. RBC and sympathomimetic amines. SETTING: Clinical study during a four year period. PATIENTS (mean +/- SD): Group I included 50 consecutive FAP ATTR Met 30 recipients of first transplantation. Age was 35.3 +/- 7.1 years, neurological score 34.3 +/- 13 in 100 and time elapsed from first symptom 5.0 +/- 2.7 years. Group II (control), not different concerning age and sex, included 51 patients transplanted during the same period with other pathologies. METHOD: Anaesthetic protocol, monitoring and surgical techniques were similar in both groups. Data of the two groups were compared either by the Student's t-test or Fisher's exact test. RESULTS: Low values of systemic vascular resistance index were observed in both groups, with no differences between them. Systemic arterial pressures were usually lower in group I, because cardiac index and heart rate were also significantly lower, although within normal values. However, in group I, isoflurane (a vasodilator anaesthetic) was used during less time (p < 0.05) and in lower concentrations (p < 0.01) and phenylephrine was necessary in 26% of patients vs 0 patients in group II (p < 0.001). CONCLUSION: FAP patients presented a different intraoperative behaviour when compared to other patients submitted to liver transplantation. From a clinical point of view, the authors stress: 1--As a result of autonomic dysfunction, the administration of anaesthetic drugs to FAP patients always presents the risk of producing significant hypotension; even the use of ketamine does not prevent hypotension; 2--Safety is ensured by beat-to-beat surveillance of arterial pressures and the capacity to act immediately to support circulation; 3--These patients seem to be very sensitive to decreases in the pre-load; 4--Hypotension is also frequent with an adequate pre-load, usually as the result of low SVR; an infusion of a vasoconstrictor drug emerges as the most frequent treatment requested and our experience supports it as an effective one.